Sequência didática para estudar o comportamento da luz através de experimentos - Fajardo, Gledson Gonçalves (2021)
Teaching concepts of physical optics to high school students, especially those related to the behavior of light, is not a simple task. The approach to these topics is scarce, and short class time during the week are the challenges encountered. The use of experiments in the classroom is a good tool to be used to approach these subjects, mainly in the 3rd year of high school, where the subjects of modern physics are also little explored. With the use of experiments, we have the students' motivation and engagement as an additional stimulus in the presentation of the studied subjects. The purpose of this work was to develop a didactic sequence for the study of the behavior of light with experiments, the contents covered involve concepts of optics and modern physics. Our goal is to offer high school teachers alternatives to stimulate their students through practical activities appropriate to each reality. Our methodology was guided by David Ausubel's theory of Significant Learning, in the sense that the student is stimulated with a potentially significant product. The product was applied to a 3rd year high school class at a state school in the interior of the state of São Paulo. The product was developed in stages: survey of previous knowledge about the behavior of light, conducting experiments on this theme and a final questionnaire on understanding the theme. The experiments involved topics such as refraction, diffraction, interference and the photoelectric effect, all of which allowed students to discuss the concepts of the wave and corpuscular behavior of light and build their knowledge about the contents covered, in the student's notebook of modern optics and physics. From the final questionnaire and the interaction in practical experimental activities during the sequence, it was possible to verify the students' motivation and interest in the subjects covered in each experiment. The product allowed the emergence of questions, raising hypotheses and debates about the observed phenomena associated with the behavior of light.